A Comparison of Problem Solving Strategies of Primary School 3rd and 4th Graders - Halil Önal (Universitas Pendidikan Indonesia, 2023)
The aim of the study is to find out the problem-solving strategies used by primary school 3rd and 4th-graders in solving non-routine problems. The basic qualitative research design, one of the qualitative research approaches, was used in the research. The participants of the research consisted of 216 students, 104 of them in the third-grade and 112 of them in the fourth-grade. The